Sensing with toroidal metamaterial - Gupta, Manoj (2017)
Localized electromagnetic excitation in the form of toroidal dipoles has recently been observed in metamaterial systems. The origin of the toroidal dipole lies in the currents flowing on the surface of a torus. Thus, the exotic toroidal excitations play an important role in determining the optical properties of a system. Toroidal dipoles also contribute towards enabling high quality factor subwavelength resonances in metamaterial systems which could be an excellent platform for probing the light matter interaction. Here, we demonstrate sensing with toroidal resonance in a two-dimensional terahertz metamaterial in which a pair of mirrored asymmetric Fano resonators possesses anti-aligned magnetic moments at an electromagnetic resonance that gives rise to a toroidal dipole. Our proof of concept demonstration opens up an avenue to explore the interaction of matter with toroidal multipoles that could have strong applications in the sensing of dielectrics and biomolecules.